The Effect Of Applying Hassle Line Strategy Assisted By Kine Master On The Students’ Speaking Achievement - Rismadila R (Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of this study was to find out effect of applying Hassle Line Strategy Assisted by Kine Master to increase the students‟ speaking skill and to find out students‟ speaking skill better taught by Hassle Line Strategy Assisted by Kine Master than conventional method. The research design in this research was quantitative experimental research. The instrument to collect the data was test by oral test. The technique taken sample used Cluster Random sampling to determine the control and the experimental group. In addition, there were pre-test, treatment and post-test in both of the groups. It was conducted at the seventh grade students of SMP Negeri 17 Medan. The result showed that the t-test was 11.9 and the t[1]table was 1.67 which was used 0.05 as the significant level of this research. Because the t-test value is higher than the t-table (11.9 1.67), it showed that the result in t-test was accepted (Ha). Based on the result of this research, it can be concluded that there was significant effect of applying Hassle Line Strategy Assisted by Kine Master on the students‟ achievement in speaking which made the students more enjoyable and deep understanding in material. Indeed, it is recommended for teachers to apply this strategy in teaching English, especially in teaching speaking.